Introduction: Buddhist funeral cultures - Ladwig, P.; Williams, John (2012)
© Cambridge University Press 2012. Death at the centre of buddhist culture the statement that “death is the origin and the center of culture’ (Assmann 2005: 1) might at first sight seem like a simple generalisation that misses out on many other aspects of culture. However, when the study of death is not simply reduced to a rite of passage, we believe that approaching Buddhist cultures through their ideas, imaginaries and practices related to death can help us to understand crucial facts that reach beyond the domain of death and dying. First, death offers a unique departure for understanding the relations between people, monks, ritual experts and other entities that are commonly labelled as “the dead’, but can in fact comprise a multitude of entities of various ontological statuses. Second, death reaches out into such diverse domains as agricultural fertility, human reproduction, political cults and the economy and therefore constitutes a total social fact (Mauss 1990). Jan Assmann’s statement also has a particular relevance for the history of Buddhism. Death indeed was and is at the centre of Buddhist culture and has on a ritual, ideological and even economic level played a crucial role in its development and spread. Death was from its beginning an event that was seen as particularly central to Buddhist interests. Throughout Asia it has always been recognised that Buddhists are specialists in death. One of the things that attracted Chinese (and Tibetans, for that matter) to Buddhism was its clarity about what happens at death, the processes needed to ensure a successful death – the welfare of the dead person and his or her mourners – and its clarity about what happens after death and its links with the whole way someone has lived their life. No other rival religion in Asia had at that time such clarity. It was a major factor in the successful transmission of Buddhism from its original Indian cultural context.